Resiliência de pontes frente a eventos hidrodinâmicos extremos: lições das inundações de 2024 no RS - Chicherit, Yamila Soledad (2025)
The study will investigate the resilience of bridges to extreme hydrodynamic events, using the floods that occurred in Rio Grande do Sul between April and May 2024 as a basis. The central objective of the research will be to assess the hydrological and geomorphological conditions that led to the structural failure of several bridges in the region, identifying the main collapse mechanisms and proposing normative and structural improvements to enhance infrastructure resilience against future extreme events. To achieve this, geomorphological analyses, hydrological and hydraulic modeling will be conducted, allowing for a discussion of factors such as climate change, erosion, and compliance with technical standards. The results will help characterize the impacts of the floods on the bridges and identify relevant structural vulnerabilities. Additionally, the research will provide a better understanding of the interaction between river dynamics and affected structures, offering insights that may be useful for future studies and planning aimed at risk mitigation and the adaptation of road infrastructure to extreme events.